It was a woman's body... - Rocha, Ewelter (GIS - Gesture, Image and Sound - Anthropology Journal, 2016)
The audiovisual essay, “It was a woman’s body...,” consists of an audiovisual ethnographic writing experience, whose form has been conceived under the auspices of such intension. From that perspective, we have developed a narrative in which sounds, images, texts and speech are intertwined for the construction of a combination that favors overlapping, in the same support, the memory of an ethnographic experience and the artistic production that represents its main protagonists. In this case, by focusing on the wooden sculptures and the clay pieces that portray the beatas (Brazilian Catholic women extremely dedicated to religious obligations) from Juazeiro do Norte – CE.Translation: Tânia Caldashttps://vimeo.com/175552589